Methodology to monitor strategic risks (Revista de Investigaciones Universidad del Quindío, 2017)
This paper presents the advances in the research Methodology to monitor strategic risks done by the Universidad EAFIT Research Group on Information and Management. The objective of the research is to design a methodology that allows monitoring different environment variables, both inside and outside the organizations, which can hinder the fulfillment of their strategic goals.This is a qualitative and exploratory study An internal and external review of documents related to different practices of organizational monitoring such as economic intelligence, competitive intelligence, early warnings, market intelligence and balanced scorecard was made in order to identify the instruments and mechanisms used in the building up of the methodology. Additionally, we studied information on monitoring from the international risk standards to contrast these results with the different monitoring practices used in the business world. The consultation on the monitoring practices was done through open and semi-structured interviews. The results of this research determine the need of having a methodology that incorporates the prerequisites for its implementation -sensitization on the importance of this practice, identification of the risks, evaluation and prioritization. That also includes the establishment of the information needs, the mechanism to monitor the prioritized risks, the search for information, its validation, analysis, and the decision making; that allow the organizations to respond to the strategic risks that can affect them.
Keywords: Risk; strategic risk; strategic monitoring; strategy